2020
DOI: 10.3390/ma13153334
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Terry Textiles with Photo- and Bio-Activity in a Model Study and Real Conditions

Abstract: The aim of the study was to assess the photocatalytic (decompose staining particles, K/S values, the color differences, CIE L*a*b* color) and antimicrobial properties of textiles modified with TiO2 and ZnO nanoparticles (NPs) confirmed by X-ray diffraction, dynamic light scattering, SEM-EDX) in visible light conditions. The antimicrobial effectiveness of modified textiles under model conditions has been reported against 5 microorganisms: Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Candida albic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…In earlier research in the photocatalytically modified textiles model conditions, low and medium antimicrobial activity (A = 0.40-1.62) was observed towards the tested microorganisms: E. coli, S. aureus., B. subtilis, C. albicans, and A. niger [33]. In the present study, for the same microorganisms, higher antimicrobial activity was observed, mainly medium and high (A = 1.3-8.0) with the exception of low biostatic effect under conditions of lower light intensity 400 µW/cm 2 for B. subtilis, A. niger, and C. albicans (A = 0.46-0.96).…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In earlier research in the photocatalytically modified textiles model conditions, low and medium antimicrobial activity (A = 0.40-1.62) was observed towards the tested microorganisms: E. coli, S. aureus., B. subtilis, C. albicans, and A. niger [33]. In the present study, for the same microorganisms, higher antimicrobial activity was observed, mainly medium and high (A = 1.3-8.0) with the exception of low biostatic effect under conditions of lower light intensity 400 µW/cm 2 for B. subtilis, A. niger, and C. albicans (A = 0.46-0.96).…”
Section: Discussionsupporting
confidence: 62%
“…Cotton terry towels were surface-modified using commercial dispersions of ZnO and TiO 2 NPs using the padding-squeezing method. The crystal structure of NPs in dispersion are as follows: ZnO zincite crystal structure and TiO 2 rutile crystal structure, as were indicated in our earlier studies [33]. Rutile form is a stable phase of TiO 2 [34], and zincite form of ZnO is stable in a neutral medium at temperatures up to 1100 • C [35].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations